2006
DOI: 10.1579/05-a-076.1
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Impact of Sea-level Rise on Nonmarket Lands in Singapore

Abstract: Sea-level rise, as a result of climate change, will likely inflict considerable economic consequences on coastal regions, particularly low-lying island states like Singapore. Although the literature has addressed the vulnerability of developed coastal lands, this is the first economic study to address nonmarket lands, such as beaches, marshes and mangrove estuaries. This travel cost and contingent valuation study reveals that consumers in Singapore attach considerable value to beaches. The contingent valuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…However, unintended spillover impacts from adaptation can occur. For example, tourism may significantly suffer if sea walls are built along the beaches (Ng and Mendelsohn 2006). Last, policy makers need to consider the provision of health services, food, sanitation, and water during and after a storm surge event.…”
Section: Adaptation Strategies To Storm Surgesmentioning
confidence: 99%
“…However, unintended spillover impacts from adaptation can occur. For example, tourism may significantly suffer if sea walls are built along the beaches (Ng and Mendelsohn 2006). Last, policy makers need to consider the provision of health services, food, sanitation, and water during and after a storm surge event.…”
Section: Adaptation Strategies To Storm Surgesmentioning
confidence: 99%
“…Such effects, however, have received relatively little attention in the literature and few city based studies have been undertaken. An exception is that for Singapore (Ng and Mendelsohn 2006) which estimated the economic impact of sea-level rise on land that bears no market prices, including beaches, marshes and mangroves, using non-market monetary valuation techniques. They find that local inhabitants attach considerable value to beaches and natural resources, and that protecting such land, whilst found to have sizeable costs, and being potentially harmful to some natural resources, is justified on the grounds of economic efficiency.…”
Section: Other Impactsmentioning
confidence: 99%
“…On the other hand, adaptation research over the past two decades has reported high potential and observed net benefits of adaptation strategies and measures to global warming in natural resource intensive industries (Seo and Mendelsohn ; Seo , , , ), in sea level rises (Yohe and Schlesinger ; Ng and Mendelsohn ), in heat‐related or cold‐related fatalities (Barreca et al ), and in extreme events such as tropical cyclone‐caused fatalities (Seo ; Seo and Bakkensen ). In many world regions, adaptation will make harmful effects of global warming much less severe.…”
Section: Future Directions Of Global Warming Negotiationsmentioning
confidence: 99%